Analisis Yuridis Konsolidasi Tanah Perdesaan Atas Tanah Ulayat Masyarakat - Purba, Cordyn Parulian Tuah; Idham, Idham (ARBITER: Jurnal Ilmiah Magister Hukum, 2021)
This article or writing aims to find out and analyze the legal rules governing land consolidation and how to carry out the consolidation of rural land on the ulayat lands of indigenous peoples in Samosir Regency. The problem is focused on the legal arrangements governing land consolidation and procedures for implementing land consolidation. To answer the problems in this paper, the theory of the legal system and the theory of legal certainty are used. This research uses normative legal research. In essence, normative legal research is the main legal research considering that the main source of law in the legal system that applies in Indonesia is the law. This study concludes that: The Laws governing Land Consolidation are as follows: (a) Law no. 5 of 1960 concerning Basic Regulations on Agrarian Principles; (b) Law no. 17 of 2007 concerning the National Long-Term Development Plan (RPJPN) for 2005-2025; (c) Law no. 26 of 2007 concerning Spatial Planning; (d) Law no. 1 of 2011 concerning Housing and Settlements; (e) Law no. 20 of 2011 concerning Flats; (f) Government Regulation No. 16 of 2004 concerning Land Use; (g) Presidential Regulation No. 2 of 2015 concerning the National Medium Term Development Plan (RPJMN) 2015-2019